Magister H.E. Grosmanns musikaliesamling i Århus: En Telemann-fyndgruva - Andersson, Greger; Harwell, Anna H. (Danish Yearbook of Musicology, 1995)
Magister H.B. Grosmann’s Music collection in Århus. A mine for Telemann music H.E. Grosmann (1732-1811) left a number of musical manuscripts to the Cathedral School in Århus, Denmark (now in the State Library, Århus). The majority of these manuscripts are cantatas by G.P. Telemann (22 pieces). Until now these cantatas have remained unnoticed by international surveys of Telemann’s compositions. Cantor Grosmann reworked the cantatas in varying degrees and gave them Danish texts. This article is concerned with identifying and dating the cantatas (see Appendix) as well as presenting a chain of arguments concerning the collection’s genesis. One theory states that Grosmann received the cantatas in 1760 from his old school teacher, J.C. Niemeyer in Haderslev (a trading town in Jutland). The cantatas were performed in Århus between 1760 and 1777. The Grosmann collection also contains a small number of works which possibly could be unica. It is the largest collection of Telemann cantatas in Scandinavia.